New Insight on the Sublethal Effect of Bt-Cry1Ab in Spodoptera litura (Fabricius): Tissular Distribution of Cry1Ab, Ultrastructural Alterations and the Lysosomal Response - Yan-Jue Wang; Ya-Qin Shen; Ying-Dan Xiao; Xue Yang; Shao-Peng Hao; Jian-Qiu Liu; Xiao-Xue Yang; Kazuei Mita; Ya-Jing Xu (Insects, 2024)
Bt has been applied as a gene source for insect-resistant transgenic crops, which represents efficient control of insect pests. In this study, we evaluated the pesticidal specificity of one Bt maize strain, DBN9936, that expresses Cry1Ab protein in Spodoptera litura larvae. The results showed that this Bt maize is active against the younger larvae while causing a sublethal effect on older larvae. To further assess the biological responses of S. litura under sublethal Cry1Ab exposure, the relative concentrations of Cry1Ab in different tissues of fifth instar larvae were investigated, indicating that Cry1Ab is transported along the gut and out of the body via excretion or into the hemocoel and lead to sequestration by molting. Furthermore, the result of ultrastructural observation in sublethal Cry1Ab-treated midgut, namely an increase in lysosome number, with the lysosomal activity activation simultaneously provides a strong indication that lysosome plays an active role in response to sublethal Cry1Ab exposure.